Peran pendidikan pancasila dalam mendorong partisipasi demokrasi generasi muda - Syaifullah, Syed Umar (Maliki Interdisciplinary Journal, 2025)
Pancasila Education plays an important role in shaping the character, morality, and democratic awareness of Indonesia’s young generation. As the nation’s foundational ideology and way of life, Pancasila contains the values of humanity, justice, unity, and deliberation, which serve as guidelines in social and national life. This study aims to analyze the strategic role of Pancasila Education in fostering democratic awareness and participation among young people amid the challenges of globalization. The research employs a qualitative descriptive method with a library research approach, examining various literature sources and previous studies. The results show that Pancasila Education functions not only as a normative subject but also as a means of character formation and national identity strengthening. Through learning based on Pancasila values, young people are encouraged to think critically, act tolerantly, and take responsibility in democratic life. In the era of globalization, Pancasila Education serves as an ideological safeguard against the negative influence of foreign cultures and reinforces the spirit of nationalism. Therefore, Pancasila Education must be developed adaptively and creatively to remain relevant in shaping a young generation that is full of integrity, nationalism, and strong democratic awareness to realize an Indonesian society that is just, ethical, and civilized.